In silico assessment on the binding interactions of phytochemicals from Medicago sativa leaves with myocardial infarction targets - Rengaraj GOMATHI; Hariharan USHA; Thoudam BHAIGYABATI; Sanasam SUCHITRA; Pandian PARTHIBAN (Notulae Scientia Biologicae)
Medicago sativa (alfalfa), a perennial medicinal herb, has been widely valued for its diverse therapeutic applications. This study investigated the phytochemical composition of M. sativa leaves using various solvent extraction methods, including methanol, ethanol, chloroform, ethyl acetate, and petroleum ether. Qualitative phytochemical screening revealed the presence of key bioactive constituents, which were further evaluated for their in vitro free radical scavenging potential. Additionally, in silico molecular docking studies were conducted to assess the interactions of these bioactive compounds with myocardial infarction-associated targets, including Myoglobin, Cyclooxygenase, and Coagulation Factor X. The results demonstrated that several phytochemicals exhibited significant binding affinities with these targets, underscoring their potential as lead compounds for the development of novel therapeutic agents against myocardial infarction. These findings emphasize the pharmacological significance of M. sativa and its potential for advancing cardiovascular health interventions.